Analisis Hambatan Belajar Pada Materi Trigonometri Dalam Kemampuan Pemahaman Matematis Siswa - Toto subroto; Wildatus Sholihah (Universitas Sarjanawiyata Tamansiswa, 2018)
This research aimed to explore learning obstacles when students are given a Trigonometry problem in the mathematical understanding ability. Learning obstacles are constraints faced during learning and result in less than optimal learning. The given trigonometric material is just about the number and the difference of the cosine sinus. Trigonometry material given based on students' mathematical understanding ability. The ability of mathematical understanding based on 2 indicators is the ability of instrumental understanding and the ability of relational understanding. This research was conducted on students of class XI IPA 1MAN 3 Majalengka. This research method using qualitative approach by analyzing student answer result. The results of this study found some barriers to learning both are instrumental understanding and relational understanding.